2017
DOI: 10.5539/jas.v9n8p43
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Major and Minor Elements in Maltese Sheep, Goat and Cow Milk Using Microwave Plasma-Atomic Emission Spectrophotometry

Abstract: The mineral content of milk from sheep, goats and cows bred in Malta and Gozo were determined for the first time. Two hundred and twenty samples were collected from cow, sheep and goat farms in Malta and Gozo. Ten macro and micro minerals were analysed, using microwave plasma-atomic emission spectrophotometry.No significant differences were observed between localities for the metals in the ruminant milk. Three micro minerals, Mn, Cr and Cd were not detected in the three milk types. However, most metals differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…On the other hand, enterococci and Lactococcus lactis dominated the microbiota of samples from three and two different regions during the summer, respectively. However, the physicochemical composition of Maltese cow milk was not significantly affected when milk from Malta and Gozo farms were compared in two recent studies [ 6 , 7 ]. Similar to our results, Bokulich et al [ 22 ] reported that Lactobacillus and Streptococcus species were the dominant bacteria isolated from different types of milk in regions throughout Armenia and Georgia followed by Lactococcus and Enterococcus .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, enterococci and Lactococcus lactis dominated the microbiota of samples from three and two different regions during the summer, respectively. However, the physicochemical composition of Maltese cow milk was not significantly affected when milk from Malta and Gozo farms were compared in two recent studies [ 6 , 7 ]. Similar to our results, Bokulich et al [ 22 ] reported that Lactobacillus and Streptococcus species were the dominant bacteria isolated from different types of milk in regions throughout Armenia and Georgia followed by Lactococcus and Enterococcus .…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge no information is available for the LAB diversity of raw milk from the country of Malta. The only available information about Maltese cow milk is its physicochemical characteristics [ 6 , 7 ]. To achieve our goal, the following objectives were set: (i) isolation for first time of native microbiota of raw Maltese milk with the main focus on lactic acid bacteria (ii) identification of the isolated autochthonous Maltese bacteria using molecular methods, (iii) comparison of the LAB isolated from raw Maltese milk in summer and winter and (iv) comparison of the LAB isolated from raw milk from five regions of Malta (Southern region, South-eastern region, Central region, Northern region and Gozo).…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, milk samples (2 mL) were treated with 5 % HNO 3 and heated on a hot plate for approximately 75 min. The samples were ashed at a temperature of 500 • C for 4 h and made up to a 50 mL volume by dissolving the ashes in 5 mL of 5 % nitric acid topped with deionized water (Spiteri and Attard, 2017).…”
Section: Mineral Concentrationmentioning
confidence: 99%
“…Briefly, the milk samples (2 mL) were treated with 5% HNO 3 and heated on a hot plate at 80°C for approximately 75 minutes. The samples were ashed at a temperature of 500°C for 4 hours and made up to a 50 mL volume by dissolving the ashes in 5 ml of 5% nitric acid, before being topped with deionized water (Spiteri and Attard, 2017). .…”
Section: Sample Preparationmentioning
confidence: 99%